Distinct compartmentalization of immune cells and mediators characterizes bullous pemphigoid disease. Issue 12 (28th October 2020) - Margaroli, Camilla; Bradley, Bridget; Thompson, Cecilia; Brown, Milton R.; Giacalone, Vincent D.; Bhatt, Lopa; Stoff, Benjamin; Ahuja, Sanjeev; Springman, Eric; Tirouvanziam, Rabindra; Feldman, Ron J.
Abstract: Bullous pemphigoid (BP) is an autoimmune blistering disease characterized by recruitment of leucocytes into skin and release of damaging enzymes, resulting in epidermal detachment and blister formation. To better understand the role of leukotriene B4 (LTB4) and other inflammatory factors in BP pathophysiology, we conducted microscopic and immunohistochemical analyses of preserved skin biopsy sections and conducted flow cytometry and ELISA analyses of matched blood and blister fluid from BP patients. Neutrophils predominated in BP blister fluid, which also contained monocytes/macrophages and T cells, but few to no eosinophils and B cells. In contrast, BP skin histology showed a different pattern, with abundant neutrophils but eosinophils being the predominant immune cell type. LTB4 pathway and neutrophil activation markers were prevalent in BP skin lesions and strongly associated with perivascular neutrophils. Blister fluid neutrophils, monocytes/macrophages and eosinophils all exhibited increased surface expression of leukotriene A4 hydrolase and neutrophil elastase ( P  = .002 for both). Blister fluid was also enriched in interleukins (IL)‐1α, IL‐1β, IL‐8, IL‐10, IL‐18, monocyte colony‐stimulating factor (M‐CSF) and vascular endothelial growth factor (VEGF). Our findings suggest differential leucocyte recruitment from blood into dermis and from dermis into blister, which correlates with disease activity, and presents potential new treatment opportunities for BP.